2009
DOI: 10.1371/journal.pbio.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Positional Cues in the Drosophila Nerve Cord: Semaphorins Pattern the Dorso-Ventral Axis

Abstract: Positional cues target sensory axons to appropriate volumes of the developing nervous system independently of their synaptic partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
98
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 60 publications
11
98
0
Order By: Relevance
“…The axonal terminals of C4da sensory neurons likely form synaptic connections with neurons in the VNC (7,8). To examine the synaptic connectivity patterns of C4da neurons, we visualized presynaptic terminals of C4da axons by expressing synaptotagmin-GFP (Syt-GFP) in C4da neurons.…”
Section: Asap Overexpression In V'ada Neurons Induces Ectopic Contralmentioning
confidence: 99%
See 1 more Smart Citation
“…The axonal terminals of C4da sensory neurons likely form synaptic connections with neurons in the VNC (7,8). To examine the synaptic connectivity patterns of C4da neurons, we visualized presynaptic terminals of C4da axons by expressing synaptotagmin-GFP (Syt-GFP) in C4da neurons.…”
Section: Asap Overexpression In V'ada Neurons Induces Ectopic Contralmentioning
confidence: 99%
“…The class IV dendrite arborization (C4da) sensory neurons in the Drosophila peripheral nervous system (PNS) provide an in vivo system for investigating the molecular mechanisms that regulate distinct sensory axon projections (7,8). C4da neurons comprise three subtypes positioned at distinct regions in each abdominal hemisegment: ddaC, v'ada, and vdaB ( Fig.…”
mentioning
confidence: 99%
“…Several studies have mapped the neuropilar regions in which the dendritic fields of motor neurons and the axon terminals of sensory neurons are found (Merritt and Whitington, 1995;Schrader and Merritt, 2000;Grueber et al, 2007;Zlatic et al, 2009;Wu et al, 2011). Combining this knowledge with information from the current study about interneuron axon morphology allows the identification of subsets of interneurons that may form synaptic connections with motor neurons or sensory neurons ( Fig.…”
Section: Applications Of the Databasementioning
confidence: 88%
“…B-D, Potentially connected populations of neurons. B is taken from the work of Zlatic et al (2009) with the written permission of M. Zlatic and M. Bate, University of Cambridge, Cambridge, UK, and shows functionally different neuropil areas identified by the authors: the blue area is where most motor neuron dendrites arborize; in orange is the area where proprioceptive neurons terminate; green is the termination area of mechanosensory chordotonal organ neurons and yellow depicts the termination zone of nociceptive class II-IV multidendritic neurons. C shows the interneurons that project through PC and terminate in the dendritic field of motor neurons and are therefore good candidates for input neurons.…”
Section: Applications Of the Databasementioning
confidence: 99%
“…Still unknown are the mechanisms by which Cut regulates this switch, as Pdm1/2 appear not to affect axon terminal positioning of da neurons. Prior studies have shown that axon positioning along the dorsoventral axis is controlled in part by Semaphorin-Plexin signaling (Zlatic et al, 2009), and it will be important to examine whether Cut directly or indirectly regulates this pathway to control axonal targeting.…”
Section: Discussionmentioning
confidence: 99%